Historical revisionism in foreign policy of Turkey and Serbia - Đurović, Branimir (Political Life, 2026)
The paper examines and compares the causes and consequences of the historical revisionism of Turkey and Serbia, embodied in the intense and harsh denial of the genocide committed against the Armenians in 1915 and the genocide committed against the Bosniaks in 1995, respectively. Regarding the theoretical framework, the paper applies the theory of ontological security. The theory starts from the fact that states, as well as individuals, need a stable autobiography and a solid narrative about the past and the origin of the community. That narrative and state identity are called into question when the state and its society are confronted with the crimes they committed in the past. Turkey and Serbia invest great efforts in denying the crimes of the past, thus trying to protect their identity and the narrative they have created about themselves. Despite the fact that Turkey and Serbia differ in terms of foreign policy, size, power and position in international relations, neither one nor the other suffers significant consequences of such revisionist policies.